The transition in the contribution of living aquatic resources to food security - Williams, Meryl (International Food Policy Research Institute, 1996)
The fishing industry's aggressive and expanding search for fish from the sea reached a turning point in 1990. After many years of increasing production, the global marine and inland catch from natural stocks declined from the 1989 peak of about 89 million tons to 85 million tons in 1993. Aquaculture production did not increase enough to meet the shortfall, and total production also fell in 1990 and 199. Present indications are that production from natural stocks will be below the current level in the year 2020; at best, it will maintain its present level. The author addresses five major issues: (1) maximizing the use of aquatic resources; (2) resource management; (3) intensification of fisheries exploitation; (4) integration of fisheries and aquaculture; and (5) the difficult problem of balancing national versus international interests.